PROGRESS ON DRINKING WATER QUALITY MONITORING IN THE NORTHERN PART OF NIGERIA: A CATALYST TO ACHIEVING SUSTAINABLE DEVELOPMENT GOALS - Imam, Naziru; Abdurrahman, Nuraddeen; Lawal Isah, Abdulshakur; S. Lawal, Olayide (FUDMA JOURNAL OF SCIENCES, 2023)
Access to clean water for drinking and domestic activities remains a critical issue in Nigeria, especially in the northern region. The increasing global population and importance of water for life have led to a quantitative and qualitative increase in its demand. This paper reports a comprehensive review of the quality of water sources utilized for consumption in northern Nigeria over the last decade. The report aims to serve as a reference point to assess the possibility of achieving Sustainable Development Goal 6 (clean water and sanitation) by 2030 based on the level of quality of water sources in the region. The study found that well and borehole water remain the primary sources of drinking water in northern Nigeria, with little or no established networks of pipe-borne water across the region. Significantly, 55.74% of these sources were reported to be unfit for consumption due to poor portability. Additionally, 31.14% of the water sources were categorized as fair, meaning they required additional treatment to prevent disease outbreaks and health implications due to some level of contamination that did not conform to WHO standards. The report indicates that only 13.11% of clean water is accessible to the northern Nigerian populace, making it difficult to achieve SDG goal six by 2030 unless all stakeholders take action drastically. Failure to achieve SDG goal six could also impede Nigeria’s progress towards achieving other SDGs, as they are all directly or indirectly linked to it.